2005
DOI: 10.1007/s00125-005-1763-x
|View full text |Cite
|
Sign up to set email alerts
|

Leptin resistance exacerbates diet-induced obesity and is associated with diminished maximal leptin signalling capacity in rats

Abstract: Aims/hypothesis: Leptin resistance is generally considered a consequence of obesity. We postulated that leptin resistance is associated with diminished hypothalamic leptin signalling capacity and that leptin resistance is causal to obesity. We assessed maximal leptin-mediated binding of the transcription factor signal transducer and activator of transcription 3 (STAT3), and the response to high-fat feeding in lean leptin-resistant rats. Materials and methods: Recombinant adeno-associated virus encoding rat lep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
64
2
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 27 publications
7
64
2
1
Order By: Relevance
“…In a previous study, the Scarpace lab demonstrated that when lean rats were subjected to chronic leptin overexpression, the initial decrease in body weight waned over time in association with a reduction in leptin sensitivity. When these rats were then placed on a high-fat diet, they displayed an enhanced diet-induced hyperphagia and weight gain (7). Together with the current work, these experiments indicate that by inducing leptin resistance, chronic hyperleptinemia attenuates the ability to resist diet-induced obesity.…”
supporting
confidence: 68%
“…In a previous study, the Scarpace lab demonstrated that when lean rats were subjected to chronic leptin overexpression, the initial decrease in body weight waned over time in association with a reduction in leptin sensitivity. When these rats were then placed on a high-fat diet, they displayed an enhanced diet-induced hyperphagia and weight gain (7). Together with the current work, these experiments indicate that by inducing leptin resistance, chronic hyperleptinemia attenuates the ability to resist diet-induced obesity.…”
supporting
confidence: 68%
“…We have observed similar results when leptin is centrally overexpressed in lean rats. When such rats are provided a high-fat diet, they display exacerbated weight and adiposity gain compared with high-fat-fed control rats [39]. Moreover, we have demonstrated that blockade of the leptin receptor aggravates the dietary weight gain [40].…”
Section: Discussionmentioning
confidence: 72%
“…Such leptin-induced, leptinresistant lean rats exhibited an exacerbated weight and adiposity gain on a high-fat diet compared with their respective high-fat-fed controls (3,4). Hence, leptin resistance promotes dietary obesity in lean rodents.…”
Section: Discussionmentioning
confidence: 98%
“…Leptin treatment exerts potent responses in lean rodents, producing impressive weight and fat loss (2) but is generally ineffective in rats that have diet-induced obesity due to high-fat feeding and, consequently, that are leptin resistant (3)(4)(5). The presence of this leptin resistance constitutes a major obstacle in curtailing diet-induced weight gain (6,7), and one approach to treat obesity would be to restore leptin actions or circumvent the leptin resistance in dietary obese animals.…”
mentioning
confidence: 99%